ASSESSING PROGRAM OUTCOMES ATTAINMENT IN REINFORCED CONCRETE DESIGN COURSE: A FIVE-SEMESTER LONGITUDINAL ANALYSIS - Lyn Dee Goh; Che Maznah Mat Isa; Yian Peen Woo; Suhailah Mohamad Noor (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This longitudinal study investigates the attainment of two key Program Outcomes (POs), PO2 (Problem Analysis) and PO3 (Design/Development of Solutions) in a third-year undergraduate Reinforced Concrete Design course at a Malaysian public university. Data spanning five semesters, from 20214 to 20234, were collected and analysed using both direct assessment (exam and project scores) and indirect assessment (entry-exit surveys). The study aimed to identify trends, variations, and areas for improvement in the course’s effectiveness in achieving its educational objectives. Direct assessment results revealed a fluctuating trend in PO2 attainment, with a significant decline in the most recent semester (20234). Conversely, PO3 attainment showed a generally positive trend, although with some fluctuations. The gap analysis of survey data indicated that most students perceived an improvement in their competencies upon completing the course, with a higher frequency of substantial gains in PO3 compared to PO2. The findings underscore the need for targeted interventions to address the declining trend in PO2 attainment, potentially through revisiting instructional methods and providing additional support for problem-solving skills. The study also highlights the importance of continuous assessment and improvement in engineering education to ensure that graduates are equipped with the necessary skills and knowledge to excel in the field of reinforced concrete design. The research contributes valuable insights to the ongoing conversation about enhancing the quality and effectiveness of engineering education in Malaysia.